"Contract to Volunteer": South African Community Health Worker Mobilization for Better Labor Protection. (February 2018) - Trafford, Zara; Swartz, Alison; Colvin, Christopher J.
In this paper, we explore the increasing activity around labor rights for South African community health workers (CHWs). Contextualizing this activity within broader policy and legal developments, we track the emergence of sporadic mobilizations for decent work (supported by local health activist organizations) and subsequently, the formation of a CHW union. The National Union of Care Workers of South Africa (NUCWOSA) was inaugurated in 2016, hoping to secure formal and secure employment through government and the consequent labor and occupational health protections. Various tensions were observed during fieldwork in the run up to NUCWOSA's formation and raise important questions about representation, legitimacy, and hierarchies of power. We close by offering suggestions for future research in this developing space.